PENGARUH KEAKTIFAN BERORGANISASI DAN KETERAMPILAN KOMUNIKASI INTERPERSONAL TERHADAP INDEKS PRESTASI KUMULATIF MAHASISWA PENDIDIKAN TEKNIK KEJURUAN FKIP UNS - Muhammad Iqbal; Valiant Lukad Perdana Sutrisno; Ranto Ranto (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
This study aims to determine the influence between organizational activeness and interpersonal communication skills both partially and simultaneously on the cumulative achievement index in FKIP UNS Vocational Technical Education students. This study uses a quantitative ex-post facto method. The population in this study is the administrators of the association for the 2023 period from the departments of Mechanical Engineering Education, Building Engineering Education, and Informatics Engineering Education. Sampling in this study uses a total sampling technique with a total of 153 respondents. The data collection technique uses questionnaires and documentation. The data obtained were processed through prerequisite tests consisting of normality tests, linearity tests, and multicollinearity tests. The data met the prerequisite test, a hypothesis test was carried out with multiple linear regression analysis.The results of the study showed that: (1) There is a significant influence of organizational activity and interpersonal communication skills simultaneously on the cumulative achievement index in FKIP UNS Vocational Technical Education students, this is evidenced by the F value calculated 9.354 > F table 3.06 and R square of 11.2%; (2) There was a significant influence of organizational activity on the cumulative achievement index of FKIP UNS Vocational Technical Education students with a calculated t value of 2.385 > t table t 1.65, effective contribution of 5.95% and relative contribution of 53%; (3) There was a significant influence of interpersonal communication skills on the cumulative achievement index of FKIP UNS Vocational Technical Education students with a calculated t value of 2.183 > t table 1.65, effective contribution of 5.25% and relative contribution of 47%.